Are you tuned in to others' mind? A cross-modal evaluation of affective theory of mind in people with Parkinson's disease - Elisa Menozzi; Daniela Ballotta; Francesco Cavallieri; Stefania Tocchini; Sara Contardi; Valentina Fioravanti; Franco Valzania; Paolo F. Nichelli; Francesca Benuzzi (Acta Psychologica)
Affective Theory of Mind (ToM) is the ability to understand other peoples' emotional states and feelings. Several studies showed impaired affective ToM abilities in people with Parkinson's disease (PD). However, most studies tested this ability by using single-stimulus modality tasks (visual cues). The aim of the present study was to evaluate whether affective ToM abilities are impaired in PD using multiple stimulus modalities and whether they are related to disease duration and cognitive/emotional abilities.Twenty mid-stage, non-demented people with PD and 20 matched controls were evaluated by means of two tasks requiring subjects to infer others' mental states from the eyes' expression – the Reading the Mind in the Eyes (RME) test, and from the emotional prosody – a modified version of the Reading the Mind in the Voice (RMV) test. In people with PD, cognitive function and emotional processes were assessed through cognitive tasks and batteries of facial and prosodic emotion recognition tests.Compared to controls, the PD group showed significantly impaired performances in both RME and RMV tests (p < 0.0001). Affective ToM abilities in people with PD were not correlated with cognitive function or disease duration. Visual recognition of anger and auditory recognition of fear were positively correlated with RME (p = 0.0028) and RMV (p < 0.0001) test scores, respectively.Cross-modal impairment of affective ToM abilities is a non-motor feature of PD, unrelated to disease stage or cognitive status. A dysfunctional amygdala-centred network might represent the shared bases for impairments in fear and anger recognition and affective ToM abilities in PD.